Conformational changes induced by high-pressure homogenization inhibit myosin filament formation in low ionic strength solutions. (July 2016) - Chen, Xing; Xu, Xinglian; Han, Minyi; Zhou, Guanghong; Chen, Conggui; Li, Peijun
Abstract: Myofibrillar proteins (MPs) of chicken breast are generally insoluble in water. We have developed a new method whereby MPs are solubilized in water by applying high-pressure homogenization (HPH) thus potentially enabling greater utilization of meat in various products. To clarify the mechanism of solubilization of MPs by HPH, we investigated their conformation, solubility and filament forming behavior in low ionic strength solutions induced by 15, 000 psi HPH (103 MPa). HPH induces unfolding of MPs which subsequently exposes sulfhydryl and hydrophobic groups to the surface. Our findings, determined by circular dichroism, ATR-FTIR, SDS-PAGE and LC-ESI-MS/MS analysis suggest that HPH leads to unraveling of helical structures and to formation of myosin oligomers through disulfide bond. Due to intermolecular electrostatic repulsion and physical barrier of disulfide bonds in the rod induced by HPH, we suggest that the altered myosin conformation in MPs inhibits filament formation, thus contributing to high solubility of MPs in water. Graphical abstract: Highlights: HPH led to unfolding and unraveling of helical structures of MPs. HPH exposed sulfhydryl and hydrophobic groups of MPs. HPH induced formation of soluble myosin oligomers through disulfide bond. HPH inhibited myosin filament formation in low ionic strength solution. HPH increased solubility of MPs in low ionic strength solution.